Tourism Village Development In Serdang Wetan, Tangerang: An Evaluation Of Potentials And Challenges - Roozana Maria Ritonga; Regina Jayanti Purnama Halim; Narresha Marline Subronto (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2026)
Tourism villages constitute a form of community-based tourism development that contributes to improving local livelihoods while preserving cultural and environmental resources. Serdang Wetan Tourism Village, located in Tangerang Regency, is an emerging destination with distinctive natural and cultural potentials. Nevertheless, its development process faces several challenges, such as legal constraints of Village-Owned Enterprises (BUMDes) and shifting the community’s consumptive mindset which may affect long-term sustainability. This study aims to evaluate the development of Serdang Wetan Tourism Village by identifying its key potentials and the challenges encountered in its management and development. A descriptive qualitative approach was employed, utilizing data collected through field observations, in-depth interviews with Village Head, BUMDes Management Team, and Local community leaders as well as document analysis. The results reveal that strengthening the legal status and institutional governance of the Village-Owned Enterprise is a critical prerequisite for tourism village development. In addition, improving human resource capacity and supporting infrastructure is essential to ensure the sustainability of Serdang Wetan Tourism Village.